2011
DOI: 10.1016/j.jmoldx.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Strategy for Robust Detection of Insertions, Deletions, and Point Mutations in CEBPA, a GC-Rich Content Gene, Using 454 Next-Generation Deep-Sequencing Technology

Abstract: CEBPA mutations are of prognostic relevance in acute myeloid leukemia (AML) and are currently detected using a combination of denaturing high-performance liquid chromatography (DHPLC), gene scan/fragment length analysis, and direct Sanger sequencing. Nextgeneration deep pyrosequencing, principally, allows for the highly sensitive detection of molecular mutations. However, standard 454 chemistry laboratory procedures lack efficient amplification of guaninecytosine (GC)-rich amplicons during the emulsion PCR (em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

5
5

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 17 publications
2
33
0
1
Order By: Relevance
“…9,24 In addition, we recently reported that such a technique is applicable to all PCR products. Grossmann et al 25 published a study where this assay was applied to sequence CEBPA, a gene with high GC content. Using a modified PCR setup, amplicons with up to 77% GC content were successfully processed by deep sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…9,24 In addition, we recently reported that such a technique is applicable to all PCR products. Grossmann et al 25 published a study where this assay was applied to sequence CEBPA, a gene with high GC content. Using a modified PCR setup, amplicons with up to 77% GC content were successfully processed by deep sequencing.…”
Section: Discussionmentioning
confidence: 99%
“…9,[30][31][32][33] The complete regions of CEBPA and RUNX1 were investigated by 454 deep sequencing (Roche Applied Science) as previously described. 34,35 Furthermore, ASXL1 exon 12 aberrations were investigated by Sanger sequencing. 33 The controversial ASXL1 variant p.Gly646TrpfsX12 was scored as a mutation as we and others have convincing data that this is a somatic mutation (for further details, see supplemental Methods).…”
Section: Cytogenetics and Molecular Mutation Screeningmentioning
confidence: 99%
“…An alternative emPCR protocol previously established for CEBPA (454 GS FLX Titanium chemistry) uses Additive reagent instead of water in the emPCR master mix. This protocol increases the amount of PCR product in the amplicon library by up to 4-fold (18 ). Beads enriched according to this protocol have also been analyzed on the GS Junior platform.…”
Section: Ngs Of Leukemia-associated Genes With Low Amounts Of Dnamentioning
confidence: 99%